2018
DOI: 10.1002/cbin.11001
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide identification, phylogenetic classification, and exon–intron structure characterization of the tubulin and actin genes in flax (Linum usitatissimum)

Abstract: Flax (Linum usitatissimum L.) is a valuable food and fiber crop cultivated for its quality fiber and seed oil. α-, β-, γ-tubulins and actins are the main structural proteins of the cytoskeleton. α- and γ-tubulin and actin genes have not been characterized yet in the flax genome. In this study, we have identified 6 α-tubulin genes, 13 β-tubulin genes, 2 γ-tubulin genes, and 15 actin genes in the flax genome and analyzed the phylogenetic relationships between flax and Arabidopsis thaliana tubulin and actin genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 36 publications
3
20
0
3
Order By: Relevance
“…Earlier, Bhattacharya et al (2000) reported only 1-2 copy of actin genes in green algae and 2-3 copies in bryophyta species. However, consistent with our analysis recent genome wide studies have reported 21 actin genes in maize, 15 actin genes in flax (Slajcherová et al 2012, Pydiura et al 2018. Further, our pairwise analysis showed that 10-13 rice actin gene homologs were present in twenty animal species, 10-12 homologs in seven fungal and four Protista species.…”
Section: Distribution Of Actin and Tubulin Genes In 49 Diverse Eukarysupporting
confidence: 91%
“…Earlier, Bhattacharya et al (2000) reported only 1-2 copy of actin genes in green algae and 2-3 copies in bryophyta species. However, consistent with our analysis recent genome wide studies have reported 21 actin genes in maize, 15 actin genes in flax (Slajcherová et al 2012, Pydiura et al 2018. Further, our pairwise analysis showed that 10-13 rice actin gene homologs were present in twenty animal species, 10-12 homologs in seven fungal and four Protista species.…”
Section: Distribution Of Actin and Tubulin Genes In 49 Diverse Eukarysupporting
confidence: 91%
“…In the paper of Pydiura et al () genome‐wide identification, phylogenetic classification, and exon‐intron structure characterization of the tubulin and actin genes in flax ( Linum usitatissimum ) are considered. Besides β‐tubulin genes, α‐ and γ‐tubulin and actin genes have not been characterized yet in the flax genome (Gavazzi et al, ).…”
Section: Gene Organization and Expressionmentioning
confidence: 99%
“…Результати та обговорення У попередній роботі нами опубліковані дані щодо біоінформаційного пошуку генів актину, закодованих у геномі льону-довгунця [15]. Результати оцінки особливостей екзон-інтронної структури 15-ти відібраних генів актину льону свідчать про те, що більшість їх мають 4 консервативні ділянки -екзони та 3 гіперваріабельні -інтрони.…”
Section: матеріали і методиunclassified